Edukasi Pajak UMKM: Penerapan Tarif Pajak Final 0,5% Berdasarkan Aturan Perpajakan 2025 - Dian Sulistyorini Wulandari; Benny Oktaviano; Nadia Ramadhani (Jurnal Pengabdian Masyarakat, 2026)
The community service activity entitled “MSME Tax Education: Implementation of the 0.5% Final Tax Rate Based on the 2025 Tax Regulations” aims to improve tax literacy and compliance among Micro, Small, and Medium Enterprises (MSMEs) in Bekasi Regency. The low level of understanding of tax regulations among MSME actors often becomes an obstacle in fulfilling tax obligations accurately and sustainably. Therefore, this program was designed using a participatory approach through training, mentoring, and direct simulation of digital tax systems such as e-Billing and e-Filing. The program was conducted on November 22, 2025, at Universitas Pelita Bangsa (UPB), involving lecturers, students, and 12 MSME participants. The results indicate an increase in participants’ understanding of tax obligations, from 55% before the training to 87% after the program. In addition, the Bekasi MSME Tax Forum was established as a platform for continuous learning and knowledge sharing among business actors. These findings suggest a shift from individual awareness toward collective responsibility in tax compliance. Thus, community-based tax education has proven to be effective in encouraging behavioral change and strengthening fiscal inclusion among MSMEs in a sustainable manner